PENYULUHAN LITERASI DIGITAL: OPTIMALISASI PEMANFAATAN INSTAGRAM BAGI SISWA SMP DI KOTA BANDUNG - Prihandini, Puji; Rachmaniar; Anisa, Renata (JP2N : Jurnal Pengembangan Dan Pengabdian Nusantara, 2023)
Data released by APJII (Association of Indonesian Internet Providers) states that the highest age group for internet penetration is in the teenage age range of 13-18 years. As many as 99.16 percent of that age are connected to the internet. Connectivity with high internet usage is ironically not in line with media literacy skills. This is what underlies the community service team, Faculty of Communication Sciences, Padjadjaran University in conducting media literacy counseling for teenagers. PKM activities are carried out for 8th grade students of SMP YPKKP Bandung City with the theme: optimizing Instagram users. The social media Instagram was chosen because based on data from we are social in 2022, Instagram is the social media with the second most users after WhatsApp. The PKM session activity began with filling out a questionnaire in the form of questions about the behavior of using social media by Mrs. Puji Prihandini, then followed by a lecture in the form of exposure to material on the benefits of social media and the bad effects of using social media by Mrs. Rachmaniar then followed by practical steps in creating content on Instagram by Mrs. Renata. Then the event ended with a question and answer session and a quiz. As a result, students can understand the material well and can explain Back to the benefits and bad effects of social media as well as the steps in creating useful content on Instagram. This PKM activity is still in the awareness stage of using social media and compiling content, in the future this PKM activity can be continued with contetn creator workshop.